Biogas - renewable source of energy - Rozi Liliana Berevoianu (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
Biogas is considered to be an important source of renewable energy, the production of which is on a continuous rise and which can be decisive for the elimination of fossil fuels by 2050. To reduce the negative impact of human actions on the environment, we must take measures urgent for stimulating the use of renewable energy but also for increasing awareness of the environmental crisis. The major cause of greenhouse emissions, but also of climate change, is also attributed to throwing food waste into landfills. This food waste, in addition to other plant and animal matter, constitutes an important raw material for obtaining biogas. The bioenergy thus obtained can considerably reduce greenhouse gas emissions. The production of biogas offers a multitude of advantages for the population of the whole world, for the environment and last but not least for the business environment.
Keywords: Q2; Q20; Q28; 330; biogas; renewable energy sources; biofuels; energy policy